Prevalencia de pigmentación dentaria por sulfato ferroso en pacientes pediátricos - Romero-Ramìrez, Anita Mily (2025)
Iron is a fundamental element for the proper performance of the vital functions of the human body. According to the World Health Organization (WHO), approximately four out of ten children between six and fifty-nine months of age globally presented anemia, evidencing the magnitude of this nutritional problem in early childhood. Iron supplements were widely used as a preventive and therapeutic measure against this deficiency; however, one of its main side effects was tooth pigmentation. The objective of the study was to determine the prevalence of exogenous dental pigmentation associated with ferrous sulfate consumption in pediatric patients treated at the José Leonardo Ortiz Health Center during the year 2024. Material and methods. A descriptive, cross-sectional, prospective and observational design was adopted, the sample was made up of 232 children,selected from an initial population of 538 patients, according to inclusion criteria and informed consent signed by their parents. The results showed that tooth pigmentation was present in 42.24% of the children examined. Likewise, it was observed that minors who consumed ferrous sulfate for six months concentrated the highest percentage of  pigmentation (29.31%), while the most frequent dose was syrup of one teaspoon daily (28.8%). In conclusion, the study confirmed that prolonged administration offerrous sulfate in children produced exogenous tooth pigmentation, mostly of a mild degree and associated with the time of exposure to the supplement.